The Effect of Ownership Structure on the Level of Environmental Responsibility Disclosure in Annual Report - Margono Ginting (International Journal of Economics (IJEC), 2022)
This study aims to examine the effect of ownership structure on the level of environmental responsibility disclosure in the annual report. The ownership structure consists of government ownership, managerial ownership, foreign ownership, and institutional ownership. The measurement of the level of environmental responsibility disclosure is based on the GRI Index. This study uses secondary data in the form of annual reports of companies listed on PROPER and BEI in 20 13, 201 4, and 201 5. The total sample of this research is 90 company annual reports which were selected by purposive sampling. The research method used is classical assumption test and hypothesis test with multiple linear regression method. The results of this study indicate that the variables of government ownership, foreign ownership and institutional ownership have a positive and significant effect on the level of disclosure of environmental responsibility. However, managerial ownership has no significant effect on the level of responsibility disclosure environment.